SRY-negative in 46, XX Male Testicular DSD: a case report - Nurin Aisyiyah Listyasari; Ardy Santosa; Achmad Zulfa Juniarto (Journal of Biomedicine and Translational Research, 2020)
Background: The sex determination process requires distinct signaling pathways to generate either testis or ovaries from the same precursor structures, the primordial gonad. Deviations of this signaling mechanism may result in disorders/differences of sex development (DSD). The 46, XX testicular DSD is a rare genetic condition identified by a discrepancy between genetic and phenotypic sex caused sex reversal syndrome. Case Presentation: We describe the case of a 5 years-old 46, XX boy with ambiguous genitalia. On physical examination he had severe hypospadias, bifid scrotum, micropenis and palpable bilateral testes. Cytogenetic analysis of patient reveals a 46, XX karyotype. Hormonal assay showed low level of FSH, LH and Testosterone and there was no evidence of Mullerian structures based on pelvic imaging. The histopathology of gonadal tissue showed a Leydig cell hyperplasia which gives the impression of Sertoli cell nodule. Polymerase chain reaction (PCR) analysis failed to identify the presence of SRY gene, therefore a diagnosis of 46, XX Testicular DSD with SRY-negative was established. Conclusion: This report presents a rare case of SRY-negative 46, XX Testicular DSD in a boy with ambiguous genitalia. A comprehensive management including clinical, cytogenetic and molecular analyses have indicated that undiscovered genetic or environmental factors needs to be elucidated. It is important to carry out further molecular testing to establish precise diagnosis of DSD and to provide appropriate genetic counseling for patients and their family.